2011
DOI: 10.1097/iae.0b013e3181f84fdf
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Outcomes of Intravitreal Bevacizumab (Avastin) Therapy for Polypoidal Choroidal Vasculopathy

Abstract: Intravitreal bevacizumab therapy has a favorable outcome in improving visual acuity and macular exudative changes in patients with polypoidal choroidal vasculopathy. It can also moderately reduce polypoidal lesions on indocyanine green angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 44 publications
0
33
2
Order By: Relevance
“…There are fewer studies assessing the efficacy of bevacizumab, and most of them have short follow up duration or were not performed on treatment naïve patients [164,165,166,167,168,169,170,171]. In a retrospective case control study, Cho et al .…”
Section: Treatmentmentioning
confidence: 99%
“…There are fewer studies assessing the efficacy of bevacizumab, and most of them have short follow up duration or were not performed on treatment naïve patients [164,165,166,167,168,169,170,171]. In a retrospective case control study, Cho et al .…”
Section: Treatmentmentioning
confidence: 99%
“…2 Despite the similarities in the clinical features, the efficacy of treatment, including intravitreal anti-vascular endothelial growth factor (VEGF) therapy, is different between nAMD, which is a major subgroup of exudative AMD, and PCV. 4,5 This may reflect differences in their multifactorial pathogenesis, including associated systemic disorders, cigarette smoking, and genetic factors.…”
mentioning
confidence: 98%
“…Retrospective studies with bevacizumab have shown favorable results in decreasing leakage and bleeding in eyes with PCV [13,14,15]. However, the BVN and the polyps persist in the majority of eyes, which may increase the risk of long-term recurrence of bleeding and exudation.…”
Section: Introductionmentioning
confidence: 99%